Sustainable Relationships within Organisations in an Age of Transition of Economy: Focus on Employees’ Trust in Organisations - Takuji Takemoto; Hiroko Oe; Yasuyuki Yamaoka (Britain International for Academic Research (BIAR-Publisher), 2021)
This exploratory research aims to provide an overview of employees’ current views regarding their organisations, with a focus on evaluating their trust in their workplace. A quantitative approach was applied to a dataset collected from Japanese businesspeople. From the analysis, it was found that the respondents’ perspectives differed depending on three demographic variables: gender, education, and annual income. Descriptive analysis results indicate that males express more positivity and support for the organisational directions in the new lifestyle phase resulting from the COVID-19 impact, that more highly educated respondents are more positive than other cohorts, and that higher-income respondents are more positive than others. These findings imply that organisations need to design different communicative approaches with different employee groups if they are to establish sustainable relationships with employers and cope with the disruptive environment.